PENDAMPINGAN KELOMPOK KERJA TENTANG USAHA PENINGKATAN PENDAPATAN KELUARGA SEJAHTERA (UPPKS) DI LEMBANG SEHAT KECAMATAN TONDON - Panimba, Winta; Lusdani, Westerini; Ta’dung, Yohanis Lotong (Yayasan Education and Social Center, 2024)
This service activity aims to increase the understanding and skills of Working Group (Pokja) members regarding Family Income Increase Efforts (UPPKS). This activity is carried out through the delivery of training material using lecture and discussion methods. Participants are provided with assistance that focuses on business planning to increase family income. The main aim of this activity is to provide new insight to the mothers who are members of the Working Group regarding effective strategies in increasing and increasing family income through utilizing the skills they have. It is hoped that this assistance will be able to provide appropriate direction in starting business planning, so that women who are members of the Working Group can independently develop their businesses. The results of this activity show an increase in participants' understanding and skills, as well as higher motivation in utilizing their skills to contribute to improving the family economy